Prediksi Harga Cabai Di Kota Gorontalo Menggunakan Metode Weighted Moving Average - Siska M. Igirisa; Amiruddin Amiruddin (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2022)
This study aims to describe the price of chili through technology using the Weighted Moving Average method. Chili is one of the food commodities that can affect the value of inflation. The price of chili that is less erratic and even tends to continue to increase at certain times will have a bad impact on the country and society. The on-demand chili is a type of Gorontalo local chili. Chili is one of the food products that have very fluctuating prices. The Weighted Moving Average method has a good is believed to be good in predicting chili prices at the Gorontalo City Food Service Office. At the accuracy level, the prediction of future chili prices can use the Weighted Moving Average method. It is found that the application of the Weighted Moving Average method in building a system of chili price prediction can be seen through the MAPE results. The lowest error rate indicates the third-month moving average prediction (n=3), namely 26.48%, or the accuracy rate is 73.52%. Thus, the moving average value used in the chili price prediction is an average of 3 months (n=3). Keywords: prediction, chili price, Weighted Moving Average, MAPE